Tone and affixation in Hausa - Paul Newman (LibraryPress@UF, 1986)
In terms of their tonal behavior, Hausa affixes can be divided into two types. Tone integrating affixes (TIA's), all of which are suffixes, spread their tone(s) over the stem to which they are attached, overriding lexical stem tone in the process. Tonal assignment takes place in a regular right-to-left manner. Tone non-integrating affixes (TNI's) do not affect stem tone, the tone of resultant words simply being the sum of the parts. Most inflectional and derivational suffixes in Hausa, e.g. noun plurals and verbal grades, are tone integrating. Tone non-integrating affixes include a few suffixes, e.g. :waa "participial" and -aa "feminine", and the prefixes ba- "ethnonymic" and ma- "agential/instrumental/locational". Stems in Hausa typically drop their final vowel when a TIA is added; with most, but not all, TNI's, the stem-final vowel is retained.